Development of an E-Catalog of Dutch Colonial Relics in the Bekri Region of Central Lampung as a Local History Learning Resource - Yudi Hartono; Nurfayatun Khasanah; Johan Setiawan (STAI Hubbulwathan Duri, 2025)
This research addresses the need for localized history learning resources by developing an E-catalog of Dutch Colonial Heritage in the Bekri area of Central Lampung for use in SMAN 2 Metro. The objectives are: (1) to analyze students' learning needs, (2) to design an E-catalog as a local history learning source, and (3) to assess expert and practitioner feedback on the E-catalog design. The study employs the Research and Development (RD) method. Data collection techniques include observation, interviews, questionnaires, and documentation. The validation process involves both media and material experts, followed by small group testing. The developed E-catalog showcases various Dutch colonial buildings from 1916 to 2024 in Bekri. Validation results indicate high feasibility. Material expert validation yielded an 80% score, categorized as